Optical characterization of tip bended vertically aligned carbon nanotubes array - Mohd Razib, Mohd Asyraf; Saleh, Tanveer; Islam, Saiful; Rana, Masud; Abdul Muthalif, Asan Gani (Elsevier, 2018)
Vertically Aligned Carbon Nanotube arrays (also termed as VACNTs or CNT forest) have recently found to be transformable to a reflective mirror from a naturally black absorber. The feature of improved reflectance can be attained by the controllable tip bending process using the bottom surface of a rotated cylindrical tool (the process called micro-mechanical bending (M2B)). In this paper, the polarized light reflectance of bent and compacted region of the CNT forest using M2B method has been investigated. We observed that reflectance from the processed CNT zone was highly dependent on the angle of incidence and polarization state of the incident laser. For the first time, the refractive index of the tip bent CNT forests by M2B method was investigated and found to be in a range of ∼1.8.